Balancing Optimism with Strategy: Leadership in Public Sector Automation - Forsgren, Maria; Tafvelin, Susanne; Stenling, Andreas; Haake, Ulrika (Nordic Journal of Working Life Studies, 2025)
This study explores leadership in public sector automation, considering how contextual characteristics in two Swedish municipalities interact with the evolution of leadership. Through qualitative analysis of semistructured interviews with leaders and employees in elder care, we examine leadership skills and behaviors understood as crucial for implementing medicine robots. Grounded in reflexive thematic analyses, we present six themes: (1) Tech openness, (2) Optimism toward change, (3) Collaborative coordination, (4) Training and support, (5) Instrumental understanding, and (6) Operational feedback. The main findings illustrate how leadership skills, including cultivating optimism, engaging with technology and fostering collaboration, were considered essential. While proactive leadership was limited, knowledgeable and supportive leadership was apparent. Behaviors understood as supportive included communicating purpose and providing timely education. Leadership is vital in automation implementations, requiring skills to address complexities of human–technology interaction and balancing enthusiasm for automation with strategic foresight and deep understanding of the public sector context.